Über gewisse Klassen schlichten Funktionen - Kirjatsky, E. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Г. Кирьяцкий. О некоторых классах однолистных функций E. Kirjackis. Kai kurios vienalapių funkcijų klasės